The Influence Of Digital Marketing Strategies On E- Commerce Growth - Amit Kumar Singla (Educational Administration: Theory and Practice, 2023)
Digital marketing has emerged as a pivotal force in driving growth within the e-commerce sector. This paper examines the transformative role of digital marketing strategies in enhancing online visibility, engaging consumers, and fostering sustainable business growth. With the integration of advanced technologies such as artificial intelligence, machine learning, and big data analytics, businesses are able to predict consumer behavior, personalize experiences, and optimize campaigns for maximum efficiency. The study delves into key strategies, including search engine optimization (SEO), pay-per-click (PPC) advertising, social media marketing, and content marketing, highlighting their effectiveness in addressing customer acquisition, retention, and conversion challenges. Furthermore, this research explores the evolving landscape of digital marketing, emphasizing its potential to overcome barriers and capitalize on opportunities within the competitive e-commerce environment. By analyzing current trends and practices, this study provides actionable insights for businesses aiming to leverage digital marketing as a cornerstone of their e-commerce success.